Results of the Max Page muscle sliding operation for the treatment of Volkmann’s ischemic contracture of the forearm - Sharma, Pulak (Springer International Publishing, 2012)
BACKGROUND: Volkmann’s ischemic contracture is a less common but crippling condition affecting the extremities. Once the condition sets in, the prognosis always remains guarded, even after long and intensive physiotherapy and various restorative surgical techniques. This study was undertaken to evaluate the long-term functional results of the Max Page muscle slide operation in patients with Volkmann’s ischemic contracture of the forearm of moderate degree (Tsuge classification). MATERIALS AND METHODS: Nineteen patients treated between 1997 and 2009 were evaluated. The functional outcome (measured as the dexterity score, hand grip strength, sensibility, and appearance) was analyzed postoperatively. The pre- and postoperative values were compared using a paired t test. The final results were graded as good, fair, and poor. RESULTS: The average age at the time of presentation was 18 years (range 3–25 years). Tight external splintage for injuries around elbow and forearm was the primary factor. The mean period of follow-up was 3.53 years. Fifteen patients were able to achieve good functional results. Three had fair and one had poor results. All three variables showed significant improvements postoperatively. Wound dehiscence was the most common complication. One patient needed a second surgery to restore good hand function. CONCLUSION: The Max Page muscle sliding operation to treat Volkmann’s ischemic contracture of moderate degree gives good functional results. The procedure is simple and easy to perform. Adequate muscle release and proper postoperative physiotherapy are key to achieving good results.